Determination of prebiotic activity and probiotic encapsulation ability of inulin type fructans obtained from Inula helenium roots - Meral, Hilal Dikmen; Ozcan, Fahriye Seyma; Ozcan, Nihat; Bozkurt, Fatih; Sagdic, Osman (WILEY, 2024)
Inulin, a prebiotic utilized in the food and pharmaceutical industries, promotes the growth of beneficial bacteria in the colon, thereby enhancing human health. Although inulin is commercially produced from chicory and artichoke, Inula helenium roots offer a high potential for inulin production. The aim of this study is to investigate the prebiotic activity of inulin (inulin-P) from I. helenium roots on Lactobacillus rhamnosus, as well as its ability to produce synbiotic microcapsules and the effects on probiotic viability during freeze-drying, in vitro gastrointestinal (GI) digestion, and storage. First, the effect of inulin-P on L. rhamnosus viability and short-chain fatty acid (SCFA) production was compared to other commonly utilized prebiotics. The findings revealed that inulin-P remarkably promoted the growth and SCFA yield of L. rhamnosus for 48 h of fermentation and 28 days of storage. Then, L. rhamnosus was encapsulated with inulin-P and commercial inulin to compare its survival throughout storage and the GI tract. Inulin-P microcapsules outperformed in terms of viability during storage (7.98 log CFU/g after 30 days at 4 degrees C). Furthermore, inulin-P microcapsules were heat-resistant and protected L. rhamnosus from GI conditions, resulting in a high survival rate (89.52%) following large intestine simulation, which is ideal for increasing customer benefits. Additionally, inulin-P microcapsules exhibited similar physical characteristics to commercial inulin. Consequently, this study revealed that inulin-P, which is easy to produce, low-cost, and has industrial application potential, could be used as a good carrier for the synbiotic encapsulation of L. rhamnosus. Practical Application: Inulin is a prebiotic that promotes the activity and growth of beneficial bacteria in the human gut. Although commercial inulin is currently produced from chicory root and artichoke, Inula helenium root is a potential raw material for inulin production. In this study, inulin was produced from I. helenium roots with a low-cost and easy production method, and it was determined that this inulin was an effective carrier in the synbiotic encapsulation of L. rhamnosus.
Keywords: microencapsulation; prebiotic activity; bioavailability; probiotic; LACTOBACILLUS-RHAMNOSUS; SURVIVAL; VIABILITY; BIFIDOBACTERIA; SALIVARIUS; DELIVERY; PECTIN; STARCH; Food Science & Technology